Is aerobic combined with resistance training a more suitable exercise program for obese college students? Evidence-based on subjective reports and objective measurements - Li, Yan; Hu, Yanbin (Frontiers in Physiology, 2025)
ObjectiveThis study aims to investigate the exercise programs that are more suitable for obese college students.MethodsA randomized controlled experimental design was used to randomly divide 57 obese college students into Baduanjin combined resistance training group (BRTG, n = 19), resistance training group (RTG, n = 19), and control group (CG, n = 19).Results1) After an 8-week intervention, BMI, PBF, and VFI of BRTG and RTG significantly decreased, while MM significantly increased; Meanwhile, PBF and MM of BRTG were significantly lower than that of RTG. 2) The SDNN, RMSSD, and HFnorm of BRTG and RTG were significantly increased after intervention, and LFnorm and LF/HF of BRTG and RTG were significantly decreased; Meanwhile, LFnorm and LF/HF of BRTG were significantly lower than RTG, while HFnorm was significantly higher than RTG. 3) The TC, TG, and LDL-C of BRTG and RTG were significantly decreased, while HDL-C was significantly increased after intervention. 4) Compared with single resistance training, Baduanjin combined with resistance training intervention is more conducive to enhancing the subjective exercise experience and compliance of obese college students.ConclusionModerate-intensity aerobic combined with resistance training is a more suitable exercise program for obese college students and has greater application potential in health promotion.